2011
DOI: 10.1016/j.biosystemseng.2011.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating whole field irrigation performance using statistical inference of inter-furrow infiltration variation

Abstract: Inter-furrow infiltration variability is often ignored during the evaluation and optimisation of furrow irrigation. Existing techniques for estimating infiltration parameters are generally too intensive in measurement and computation for routine application at the field scale and have therefore primarily been used to study the behaviour of single furrows. This paper identifies the inter-furrow infiltration variation within typical furrow-irrigated fields and determines that this variation can be adequately des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Infiltration properties are the most significant soil parameters in the simulation, design and evaluation of surface irrigation methods (Holzapfel et al, ; Berehe et al, ). Even for the same type of soil, infiltration properties can differ with different irrigation methods (Gillis et al, ). In surface irrigation, the advance of the water and the recession after the time of cutoff will be influenced by the infiltration of the water (Elliott and Walker, ; Bakker et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Infiltration properties are the most significant soil parameters in the simulation, design and evaluation of surface irrigation methods (Holzapfel et al, ; Berehe et al, ). Even for the same type of soil, infiltration properties can differ with different irrigation methods (Gillis et al, ). In surface irrigation, the advance of the water and the recession after the time of cutoff will be influenced by the infiltration of the water (Elliott and Walker, ; Bakker et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, many researchers clearly demonstrated that soil infiltration parameters and Manning roughness vary considerably between the furrows within the same field (Schwankl et al, 2000;Oyonarte & Mateos, 2003;Mateos & Oyonarte, 2005;Wang et al, 2009;Zhu et al, 2009;Gillies et al, 2011), and indicated that the variations between furrows are significant factors for the advance trajectory and performance of surface irrigation. Previous researches have often used representative values of infiltration parameters and roughness to simulate the advance trajectory and performance for the whole field scale, thereby ignore the inter-furrow variability (Álvarez, 2003;Eldeiry et al, 2005;Sánchez et al, 2009;Reddy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Two important factors which fall into the latter category are soil infiltration and surface roughness. Unfortunately these factors are not simple to quantify and can vary significantly over space and time (Gillies et al 2011). Simulation models can be used in a rough investigative manner with generic soil intake parameters.…”
Section: The Inverse Solution Approachmentioning
confidence: 99%